Relationship of Organizational Justice with Constructive Deviant Behavior in Manufacturing Organizations - Riasudeen, S.; Narayanan, Kanimozhi (Prabandhan: Indian Journal of Management, 2015)
The research paper aims to determine the relationship between organizational justice and constructive deviant behavior. Analytical and descriptive design has been adopted to determine the relationship between organizational justice and the various dimensions of deviant behaviours. The sample of the study consisted of 109 employees from the manufacturing firms. The results indicate that the attributes of organizational justice, that is, procedural, informational, and distributive justice significantly differ from the challenging constructive deviant behavior. One of the dimensions of constructive deviant behavior and interpersonal and informational justice significantly differ from the dimension of innovative and interpersonal constructive deviant behavior. The study also reveals that the experience of the employees with respect to their age, number of dependents, marital status, and designation had significant differences with both organizational justice and constructive deviant behavior, and it was also revealed that gender had significant differences with constructive deviant behavior.